Experimental study on shear strengthening of RC beams with basalt FRP strips using different wrapping methods - Ali Saribiyik; Bassel Abodan; Muhammed Talha Balci (Engineering Science and Technology, an International Journal, 2021)
This paper presents experimental and analytical studies on the shear strengthening of reinforced concrete (RC) beams by basalt fiber reinforced polymer (BFRP) composites. The effects of BFRP composite and wrapping methods are investigated on shear strengthening of RC beams. In addition, the calculation methods suitable for these strengthening methods are investigated by comparing the results of the experimental study with the existing calculation methods. The beams with rectangular cross section were produced with steel reinforcement and low strength concrete and designed to have a sufficient flexural moment capacity but insufficient shear capacity. However, that beams with two shear regions are designed to be one side shear strength sufficient and the other side insufficient. The shear insufficient regions of the RC beams were strengthened with BFRP composites; full wrapping, side bonding and strips methods. Specimens were tested by four-point flexural test under monotonic loading. The change in shear strength, deflections, shear crack opening and shear deformations were investigated from the results of the experiment. According to the experimental results, the shear capacity of RC beams strengthened with BFRP composites increased between 43% and 100%. The best results were gained by fully wrapped sheets and fully wrapped strips configurations among strengthening configurations. In addition, an appropriate prediction model has been determined to the shear strengthening configurations.